Quality And Shelf-Life Of Mango (Mangifera Indica L.) Cv. Alphonso As Influenced By Mulching And Pre-Harvest Spray Of Chemicals And Bio-Inoculant (Pseudomonas Fluorescens) (Applied Biological Research, 2016)
Investigations were undertaken to assess the effects of mulching, bio inoculants and inorganic chemicals on shelf-life of mango cv. Alphonso.Anthracnose  Pre-harvest sprays with bio-inoculant (Pseudomonas fluorescens FP7  along with chitin) were sprayed six times at 15 days interval starting  from 15 days before expected flowering time of mango trees. Calcium  chloride (2, 4 and 6%), calcium nitrate (4%), potassium sulphate (1%)  and borax (1%) were sprayed 30 days prior to harvest. Highest tree  height, tree girth and tree spread were observed when mulching with  mango dried leaves was done along with spraying of Pseudomonas  fluorescens FP7 (0.2%) with chitin (0.5%) and 1% CaCl2. At post harvest stage the same treatment exhibited delayed ripening, lowest  physiological loss in weight, reduced anthracnose infection, increased  duration for degreening and resulted in extended shelf- life. It also  registered the highest TSS, reducing sugars, non-reducing and total  sugars, lowest titrable acidity, ascorbic acid content at the end of storage  period of 15.20 days.
Keywords: Anthracnose; bio-inoculants; chemicals; quality; PLW and shelf-life